Millions reached by a radio campaign on climate change adaptation and mitigation in the Philippines - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
CCAFS, together with the Philippine Federation of Rural Broadcasters (PFRB), implemented a radio campaign called, “Climate Change i-Broadkas Mo”(Let’s disseminate) that informed rural communities about CSA principles and practice. A set of 156 expert interviews and 165 scripts in local languages were prepared and distributed to 153 rural broadcasters. These were aired in at least 63 radio stations nationwide, reaching an estimated two million listeners. An offshoot school-on the-air program was recently launched with more than 10,000 farmer enrollees.